Determination of Tear Lipid Film Thickness Based on a Reflected Placido Disk Tear Film Analyzer - Fu, Pin-I (Diagnostics (Basel), 2020)
This study aims at determining the thickness of the tear lipid layer (LL) observed from a placido-disc-based tear film analyzer. We prospectively collected reflections of placido-disk LL images using a tear film analyzer (Keratograph(®) 5M, Oculus) from subjects with dry eye symptoms. The LL thickness (LLT) over the inferior half of the cornea was estimated with the use of interference color analysis and the preprocessing of images with and without ring segmentation were obtained and analyzed. Moreover, LLTs before and after 1 h of applying topical ointment (Duratears, Alcon) were compared to validate the estimation of LLT. Our results suggested that the tear LLT can be assessed using a placido-disk-based tear film analyzer and interference color analysis. We verified a high correlation between non-segmented and segmented LL images and estimated LLT increase after applying ointment. In addition, we concluded that LLT can be evaluated by direct interference analysis without segmentation preprocessing.